Chronic Fatigue Syndrome: Insights and Treatment Perspectives – a literature review - Ślesicka, Iga; Przestrzelska, Magda; Zozula, Natalia; Tomczewska, Zuzanna; Rykucka, Aleksandra; Wąs, Marcin; Latała, Aleksandra; Kiełbasa, Justyna; Kowalczyk, Agata; Bil, Katarzyna (Quality in Sport, 2024)
Introduction: Chronic Fatigue Syndrome (CFS) is an exhausting continuous medical condition. In most cases it affects patients after a flu-like infection. CFS correlates with alterations in the nervous and immune systems, metabolism, and hormone secretion. Diagnostic process is very challenging due to the absence of a definitive diagnostic test and wide symptomatology. It negatively impacts people's both mental and physical health. Aim of the study: The aim of this literature review is to comprehensively examine current research findings and literature on Chronic Fatigue Syndrome (CFS), understand its etiology, how it affects the body, why it's challenging to diagnose, the various treatments available, new ideas and viewpoints in the field. Describing the State of Knowledge: Despite extensive investigation, the exact etiology of CFS remains unknown. In literature CFS is also often described as Myalgic Encephalomyelitis. In the WHO's most recent classification, the ICD-11, both Chronic Fatigue Syndrome and Myalgic Encephalomyelitis are classified as “other disorders of the nervous system” which indicates the significance of the issue. Conclusions: This literature review underlines the importance of a comprehensive and collaborative approach in addressing the complexities of CFS and improving outcomes for individuals living with this debilitating condition.